Pengembangan LKPD Berdiferensiasi Pada Materi Mitigasi Bencana Alam di SMAN 4 Jeneponto - Hamka, Nurul Eka Pratiwi; H, Hasriyanti; Syarif, Erman (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to develop a valid and effective differentiated student worksheet (LKPD) on natural disaster mitigation for use in geography subject at SMAN 4 Jeneponto. The development process followed a research and development (RD) approach, involving teachers and students as test subjects. The initial needs analysis indicated a demand for differentiated instructional materials in the disaster mitigation topic. The student worksheet was designed based on specific learning objectives and differentiated learning principles. The development phase consisted of expert validation and readability testing. Expert validation results confirmed the student worksheet’s feasibility for educational use, with content, design, and language experts rating it as highly appropriate, achieving average scores of 94.64%, 90.62%, and 97%, respectively. Revisions were made based on expert feedback. The validated student worksheet was then subjected to readability testing with geography teachers and students, yielding excellent responses with average scores of 93% and 89.31%. Final refinements were implemented based on user feedback. These findings indicate that the developed differentiated student worksheet is suitable for use in geography education, particularly in teaching natural disaster mitigation.